Continuous thermally regenerative electrochemical systems for directly converting low-grade heat to electricity. (October 2022) - Li, Xiaoya; Li, Jia; Yun, Jeonghun; Wu, Angyin; Gao, Caitian; Lee, Seok Woo
Abstract: Thermally regenerative electrochemical cycle (TREC) system, which converts heat to electricity by charging at a lower voltage and discharging at a higher voltage, is a promising technology with high energy conversion efficiency for low-grade heat recovery. However, its charging process consumes additional energy and breaks the continuity of power generation. Herein, we present a continuously operated TREC system for direct heat-to-electricity conversion. In this system, two identical electrochemical cells operating at different temperatures are combined in a unit; thus, electricity can be generated continuously by periodically alternating between two temperatures. This concept is mainly demonstrated with a copper hexacyanoferrate cathode and a Cu/Cu 2+ anode, with this system achieving an energy conversion efficiency of 1.76% (14.19% of Carnot efficiency) when operated between 10 and 50 °C without heat recuperation effects. Even at an ultralow temperature difference of 10 °C vs room temperature, its efficiency is 0.98%. The proposed system allows great freedom in electrode material selection as proven by another system with nickel hexacyanoferrate cathode and Ag/AgCl anode, thereby improving the flexibility and practicability of TREC systems in low-grade heat harvesting. Graphical abstract: ga1 Highlights: Proposed continuous TREC system for direct low-grade thermal energy conversion. Experimentally achieved thermal efficiency of 1.76% and power density of 130 mW m − 2 . At 80% heat recuperation, energy conversion efficiency can be boosted to 5.60%. Obtained high efficiency of ~1% even at ultralow temperature differences of 10 °C. The system is flexible, cost-effective and scalable, advancing its practicability.